Sperm membrane functionality in the dog assessed by flow cytometry - Cheuquemán, Carolina (2012)
The objective assessment of sperm function increases the chances of predicting the fertilizing capacity of a fresh semen sample or diagnosing infertility problems. In this study, the available flow cytometry technique was used to determine the membrane functional capacity of canine spermatozoa. The second fractions of ejaculates from six dogs were pooled, and samples (n = 26) processed to determine the variables: sperm viability and plasma membrane integrity staining; phosphatidylserine (PS) translocation by Annexin-V-FITC and PI labelling; acrosome membrane integrity by FITC-conjugated Pisum sativum agglutinin ⁄ PI labelling; and mitochondrial membrane potential (DYm) by staining with. Means for the 26 examined samples indicated that 82.66 ± 2.8% of the viable spermatozoa showed an intact plasma membrane, 8.4 ± 2.6% were moribund, 72.7 ± 16% had an intact acrosome, 80.9 ± 17% had high DYm and 8.1 ± 11% had PS translocation with a PS translocation index of 2.1 ± 3%. Motility was only correlated with PS translo-cation (R = 0.3901; p = 0.0488), and acrosome membrane integrity was correlated with PS translocation (R = 0.5816;>p = 0.0018). This study provides objective physiological data on the functional capacity of canine spermatozoa.